PENGEMBANGAN SISTEM INFORMASI MANAJEMEN ASET PADA PT SEMEN BATURAJA (PERSERO) Tbk - Irfandi, M. Harun; Safaruddin, Safaruddin; Ismi, Achmad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research is entitled Development of Asset Management Information System at Pt Semen Baturaja (Persero) Tbk. The purpose of the study was to determine the Development of Asset Management Information Systems at Pt Semen Baturaja (Persero) Tbk. PT Semen Baturaja Tbk has many assets. Especially in the field of ICT such as laptops, printers, monitors, and other items used for operations. Problems that occur such as asset data that cannot be identified directly and efficiency in the use of applications that should be optimized. That way the author develops web-based and mobile asset management applications. The method used in development is waterfall and is done in stages, so that there is no break in the flow of one with another. The result of this research is the Asset Management Development Information System at PT Semen Baturaja Tbk. The development of this application aims to make the application can be used more optimally than before.